Pengaruh Motivasi Kerja, Lingkungan Kerja, Dan Displin Kerja Terhadap Kinerja Karyawan QC Perusahaan Otomotif Di Cikarang - Wachid Hasyim; Indra Permana; Rustianah (DPPM Universitas Pelita Bangsa, 2026)
This study aims to analyze the influence of work motivation, work environment, and work discipline on employee performance in the Quality Control Department of an Automotive Company in Cikarang. This study is motivated by the importance of human resource quality in maintaining product standards and achieving company targets, amidst challenges such as excessive working hours, a less than optimal work environment, and weak discipline among some employees. The research method used is quantitative with a survey approach through distributing questionnaires to 98 respondents, using a simple random sampling technique. Data were processed with the help of the IBM SPSS 27.0 program. The results of the study indicate that work motivation has no influence on employee performance. Meanwhile, the work environment and work discipline have a positive and significant influence on employee performance. These findings provide important implications for company management to pay more attention to these factors as a strategy to improve employee productivity and work quality in the future.